Relationships between parents’ academic backgrounds and incomes and building students’ healthy eating habits - Hoque, Kazi Enamul (PeerJ, 2018)
Background: Building healthy eating habit is essential for all people. School and family are the prime institutions to instill this habit during early age. This study is aimed at understanding the impact of family such as parents' educations and incomes on building students' healthy eating habits. Methods: A survey on building students' eating habits was conducted among primary school students of grade 4 (11 years) and 5 (12 years) from Kulim district, Malaysia. Data from 318 respondents were analysed. Descriptive statistics were used to find the present scenario of their knowledge, attitude and practices towards their eating habits while one-way ANOVA and independent sample t-test were used to find the differences between their practices based on students' gender, parents' educations and incomes. Results: The study finds that the students have a good knowledge of types of healthy food but yet their preferences are towards the unhealthy food. Though the students' gender and parents' educations are not found significantly related to students' knowledge, attitude and practices towards healthy eating habits, parents' incomes have significant influence on promoting the healthy eating habit. Discussion: Findings of this study can be useful to guide parents in healthy food choices and suggest them to be models to their children in building healthy eating habits.